Critical care bed capacity in Asian countries and regions before and during the COVID-19 pandemic: an observational study - Phua, Jason; Kulkarni, Atul P; Mizota, Toshiyuki; Reza Hashemian, Seyed Mohammad; Won, Yeon Lee; Permpikul, Chairrat; Chittawatanarat, Kaweesak; Nitikaroon, Phongsak; M. Arabi, Yaseen; Wen, Feng Fang; Konkayev, Aidos; Hashmi, Madiha; et al. (Elsevier, 2023)
Background The coronavirus disease 2019 (COVID-19) pandemic highlighted the importance of critical care. The aim of the current study was to compare the number of adult critical care beds in relation to population size in Asian countries and regions before (2017) and during (2022) the pandemic. Methods This observational study collected data closest to 2022 on critical care beds (intensive care units and intermediate care units) in 12 middle-income and 7 high-income economies (using the 2022–2023 World Bank classification), through a mix of methods including government sources, national critical care societies, personal contacts, and data extrapolation. Data were compared with a prior study from 2017 of the same countries and regions. Findings The cumulative number of critical care beds per 100,000 population increased from 3.0 in 2017 to 9.4 in 2022 (p = 0.003). The median figure for middle-income economies increased from 2.6 (interquartile range [IQR] 1.7–7.8) to 6.6 (IQR 2.2–13.3), and that for high-income economies increased from 11.4 (IQR 7.3–22.8) to 13.9 (IQR 10.7–21.7). Only 3 countries did not see a rise in bed capacity. Where data were available in 2022, 10.9% of critical care beds were in single rooms (median 5.0% in middle-income and 20.3% in high-income economies), and 5.3% had negative pressure (median 0.7% in middle-income and 18.5% in high-income economies). Interpretation Critical care bed capacity in the studied Asian countries and regions increased close to three-fold from 2017 to 2022. Much of this increase was attributed to middle-income economies, but substantial heterogeneity exists.